Participatory management in a high value small-scale fishery in the Mediterranean Sea. (14th September 2018) - Maravelias, Christos D; Vasilakopoulos, Paraskevas; Kalogirou, Stefanos
Abstract: In the Mediterranean Sea, the dominant type of fisheries is small-scale. Coastal communities remain dependent on fisheries for their income, some of them with limited potential for economic diversification. The top-down micro-management regime has proven ineffective to secure ecological and social sustainability as it lacks flexibility and adaptation to local and regional conditions. This paper explores the advantages of using a participatory approach and a bio-economic model to develop management scenarios in a high value small-scale shrimp trap fishery in Greece. Seeking active stakeholder involvement throughout the management process advanced the identification of management measures aiming at MSY, with high levels of acceptance from stakeholders. It also increased transparency and legitimacy of the proposed management measures and could be considered as a first step towards co-management and regionalization. The participatory approach undertaken could promote compliance and facilitate the transition to sustainable fishing, ensuring the viability of coastal communities and, thus, social sustainability.